Move to the Beat—Rhythms of Change and Firm Performance - Klarner, Patricia; Raisch, Sebastian (Academy of Management Journal, 2013)
This study examines how different rhythms of change relate to firm performance. An explorative analysis of 67 European insurance companies between 1995 and 2004 reveals that corporate strategic changes occur in four distinct rhythms, which are classified as either regular or irregular (focused, punctuated, and temporarily switching). Subsequent quantitative analysis shows that companies that change regularly outperform those that change irregularly. This finding prevails under different internal and external contingencies, under different change characteristics, and over time periods. We also find that the rhythm and frequency of change have distinct performance effects. Our findings contribute to research on the change-stability paradox by showing that a regular and sequential balance between change and stability is associated with long-term success.